Развитие профессиональной компетентности студентов будущих педагогов-психологов - Drozdikova-Zaripova, Albina R.; Kalatskaya, Natalya N. (Wydawnictwo Naukowe UAM, 2013)
This article discusses different aspects of competence and professional competence. The structure of the pedagogue- psychologist’s professional competence is presented. Forms and methods of students’ methodological and emotional competence as components of the pedagogue-psychologist’s professional competence are proposed.
Development of professionakl competences of students, future school psychologists
Keywords: competence; professional competence; pedagogue-psychologist; methodological competence; emotional competence